Insect pests associated with Andean lupin (Lupinus mutabilis Sweet) and their parasitoids in Peruvian central coast – (Lima, La Molina) - Callohuari, Y. (2018)
This survey aimed to determine the insect pests associated with Andean lupin (Lupinus mutabilis Sweet) and its parasitoids, under Peruvian central coast conditions. Sampling was made every seven days with the following methods: linear meter evaluations, plant organ evaluations, pitfall traps, and beating trays. Infested plant organs were taken to the laboratory for adult insect recovery (phytophagous or parasitoids). Pitfall traps and beating tray samples were also processed and stored. During the survey, 14,051 individuals belonging to 11 orders and 91 families were recorded. Insects that infested Andean lupin were Melanagromyza lini Spencer (stem borer), Liriomyza huidobrensis (Blanchard) (leafminer), Crocidosema aporema (Walsingham) (budborer), Grammopsoides tenuicornis (Casey) (stem borer) and Frankliniella occidentalis (Pergande) (bud and flower thrips). Diglyphus websteri (Crawford), D. begini (Ashmead), Chrysocharis flacilla (Walker), C. caribea Boucek, Chrysocharis sp. and Halticoptera arduine (Walker) were recorded as parasitoids of L. huidobrensis, whereas Carcelia sp. was recorded for C. aporema.